Sustainable polyurethane biocomposite foams by improved microstructure, acoustic characteristics, thermoregulation performance and reduced CO2 emission through phase change material integration - Gencel, Osman; Aydogmus, Ercan; Guler, Onur; Ustaoglu, Abid; Sari, Ahmet; Hekimoglu, Gokhan; Ozbakkaloglu, Togay (Elsevier, 2024)
In this research, phase change material (PCM) comprised of energy storage biocomposite materials were improved with raw materials obtained from renewable resources. Modified raw material was synthesized by epoxy castor oil (ECO). After mixing the obtained modified castor oil (MCO) and polyether polyol, PCM of capric acid (CA) was supplemented. To initiate the chemical reaction, a certain amount of methylene diphenyl diisocyanate (MDI) was added to the mixture to provide cross-linking. The physical and chemical properties of the resulting biocomposite foams (BCF) were characterized. According to the results obtained, mixing MCO into polyether raw material increased the number of closed pores in BCF resulting in more CA stored in BCF cells produced. The use of MCO in BCF materials increased the CA integration ratio to 68 wt%. The melting enthalpy value of the novel BCF-PCM composites has been determined as 121.43 J/g. In a warm environment, the PCM additive creates a temperature difference exceeding 6 degrees C, while in a cold environment, it provides a cooling effect close to 6 degrees C. A more than 50 % improvement in thermal conductivity was achieved with 68 wt% PCM addition compared to pure BCF. The addition of PCM caused a reduction in tensile stress and strain values to an acceptable level. BCFs with PCM additives exhibit a sound absorption coefficient of 0.9 in narrow frequency ranges, whereas, in broad frequency ranges, this value was more than 0.7. In cold weather conditions, employing BCFPCM material instead of traditional EPS material with a thickness of 0.1 m has led to at least a 30 % drop in CO2 emissions, no matter the type of fuel used for heating. When opting for BCF-PCM materials, the necessary heat demand was approximately 33 % less compared to using the same thickness of EPS in cold climates.
Keywords: Modified castor oil; Biocomposite foam; Renewable energy; Smart building; Energy and energy efficiency; Carbon emission